1997
DOI: 10.1097/00004424-199712000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Dendrimer-Chelates to Tumors and Tumor Cells Expressing the High-Affinity Folate Receptor

Abstract: These data demonstrate that folate-conjugated magnetic resonance imaging contrast agents represent a promising new approach to tumor targeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(138 citation statements)
references
References 9 publications
1
136
0
1
Order By: Relevance
“…The first example dealt with the targeting of tumor cells overexpressing high affinity folate receptor (hRF). Wiener et al (24) showed that the uptake of a folate-conjugated dendrimer into cells occurs with a sigmoidal dose-responsive curve, as expected for a specific uptake. The folate receptor positive cell line (8.2 ϫ 10 8 cells) was treated with 28 nM folate-conjugated PAMAM-TU-DTPAGd(III) and incubated at 37°C for 40 minutes.…”
Section: Routes For Efficient Cellular Uptake Of Gd(iii) Complexesmentioning
confidence: 78%
“…The first example dealt with the targeting of tumor cells overexpressing high affinity folate receptor (hRF). Wiener et al (24) showed that the uptake of a folate-conjugated dendrimer into cells occurs with a sigmoidal dose-responsive curve, as expected for a specific uptake. The folate receptor positive cell line (8.2 ϫ 10 8 cells) was treated with 28 nM folate-conjugated PAMAM-TU-DTPAGd(III) and incubated at 37°C for 40 minutes.…”
Section: Routes For Efficient Cellular Uptake Of Gd(iii) Complexesmentioning
confidence: 78%
“…(52)(53)(54)(55)(56) There are number of examples in the literature of efficient cellular uptake of Gd(III) complexes using Gd-DOTA derived molecules (57)(58)(59)(60). More recent efforts have sought to maximize the load of Gd delivered per receptor by tethering carrier molecules to dendridic polymers containing high numbers of Gd(III)(61), uptake through the folate receptor has been demonstrated by this means as has avidin-biotin antibody-based targeting (59,62,63). Again, definitive measurement of the amount of Gd required to produce contrast depends upon the imaging parameters employed and these must also be evaluated when testing the new contrast agents.…”
Section: Resultsmentioning
confidence: 99%
“…The interstitial residence time of the targeted agent may increase with its specific binding to the soluble form of the receptor. Ideally, the results may also be the result of specific binding of the agent to the cell surface receptor, coupled with intracellular accumulation caused by receptor recycling (28) without soluble receptor binding. Finally, a combination of binding to the cell surface receptor and the soluble receptor may also occur.…”
Section: Discussionmentioning
confidence: 99%